1999
DOI: 10.4095/219628
|View full text |Cite
|
Sign up to set email alerts
|

RADARSAT-1 Image Quality - Update

Abstract: The Canadian earth observation satellite, RADARSAT-1 was launched on November 4, 1995. Since then more than three years of successful operation have been completed, utilizing data for their intended applications. In this paper, we are primarily concerned with image quality associated with the image products generated by the Canadian Data Processing Facility (CDPF) for different SAR operating beams and modes. A chronology is presented which reviews the image quality evolution of RADARSAT-1 since launch, complem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…While the standard scenes are from one beam, the wider scenes are made from multibeam. In this case calibration is more difficult and the radiometric accuracy can be altered (Srivastava and et al, 1999;Vachon and et al, 1999). However, we found that the SAR-wind speed accuracy is the same for mono or multi-beam and the large scenes are well suited for spatial wind variability estimation over the St-Lawrence Gulf (Choisnard and et al, 2004a).…”
Section: The Sampling Approach Of Sar Scenesmentioning
confidence: 92%
“…While the standard scenes are from one beam, the wider scenes are made from multibeam. In this case calibration is more difficult and the radiometric accuracy can be altered (Srivastava and et al, 1999;Vachon and et al, 1999). However, we found that the SAR-wind speed accuracy is the same for mono or multi-beam and the large scenes are well suited for spatial wind variability estimation over the St-Lawrence Gulf (Choisnard and et al, 2004a).…”
Section: The Sampling Approach Of Sar Scenesmentioning
confidence: 92%
“…Image processing was initially conducted at the CDPF to produce SAR Georeferenced Fine (SGF) image types that have an average spatial location error (100 m and a radiometric accuracy within ¡1 dB or better in absolute levels and less than or equal to 2 dB in relative levels (Srivastava et al 1999). Further image processing was performed using the software packages, ArcView GIS and PCI Geomatica.…”
Section: Methodsmentioning
confidence: 99%
“…system (Srivastava et al 1999 , which corresponded to a decrease in fire danger conditions. The range of s o in June 2000 was again low for the mature forest (1.87 dB), moderate for the fireguard (3.61 dB), and high for the burned forest (4.74 dB).…”
Section: Image Tonementioning
confidence: 96%
“…To precisely project ground target information on pixels in the SAR image, satellite orbit information play a significantly important role. In the case of Radarsat-1, no longer operational, it had been reported that its orbit ephemeris information had locational errors of hundreds of meters and the geometric correction to correct the orbit model was necessary for the practical application of the produced SAR images [ 20 , 31 , 32 ]. However, recently provided satellite orbit information can guarantee sub-meter accuracy of sensor position.…”
Section: Error Sources For Geolocation Accuracymentioning
confidence: 99%